PROBLEMS OF INCREASING PEDAGOGICAL SKILLS OF MUSIC EDUCATION TEACHER - Turdiev Shavkat Axmedovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
a modern teacher is the creator of the future, the author, producer, researcher, user and promoter of new pedagogical technologies, theories, conceptions. Pedagogical skills of the Teacher-Organization of their forms in the most convenient and effective condition, directing them towards the goals of the fullness of personality, formation of the ability of the student worldview, awakening a tendency to the activities necessary for society are considered one of the main tasks.